Human Dignity and Human Enhancement: A Multidimensional Approach - Kirchhoffer, David G. (Bioethics, 2017)
In the debates concerning the ethics of human enhancement through biological or technological modifications, there have been several appeals to the concept of human dignity, both by those favouring such enhancement and by those opposing it. The result is the phenomenon of ‘dignity talk', where opposing sides both appeal to the concept of human dignity to ground their arguments resulting in a moral impasse. This article examines the use of the concept of human dignity in the enhancement debates and reveals that the problem of dignity talk arises because proponents of various positions tend to ground human dignity in different features of the human individual. These features include species-membership, possession of a particular capacity, a sense of self-worth, and moral behaviour. The article proposes a solution to this problem by appealing to another feature of human beings, namely their being-in-relationship-over-time. Doing so enables us to understand dignity as a concept that affirms the worth of human individuals as complex, multidimensional wholes, rather than as isolated features. Consequently, the concept of human dignity can serve both a descriptive and a normative function in the enhancement debates. At a descriptive level, asking what advocates of a position mean when they refer to human dignity will reveal what aspects of being human they deem to be most valuable. The debate can then focus on these values. The normative function, although it cannot proscribe or prescribe all enhancement, approves only those enhancements that contribute to the flourishing of human individuals as multidimensional wholes.